GASIFICATION OF WASTE OF OIL SEED COLLECTIONS IN A 20 KWe DOWNDRAFT GASIFIER - Anak Agung Putu Susastriawan (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2010)
Waste of oil seed collections, shells and deoiled cakes from current practice of bio-diesel production from Pongamia pinnata seeds, is utilized as a biomass feedstock in a 20 kWe downdraft gasifier. This gasifier is originally conventional wood gasifier. Direct use of this conventional wood gasifier for Pongamia shells leads the blocking of remaining gasified shells in grate region of gasifier reactor. This blocking is noticed as the main problem during the gasification of Pongamia shells. Gap available between the conical grate (16 cm in diameter) and inner wall of gasifier reactor at grate section is found to be too small for free flow of gasified shells. This conventional wood gasifier is modified by replacing the original conical grate with a new fabricated conical grate (15 cm in diameter). Feasibility of waste of oil seed collections for biomass feedstock of a 20 kWe downdraft gasifier is studied in present work. Performances of gasifier are compared for waste of oil seed collections and wood chips in term of calorific value of producer gas and coefficient of thermal conversion. Calorific value of producer gas from wood, Pongamia shells, and Pongamia deoiled cakes is 4.48 MJ/kg, 4.28 MJ/kg, and 2.82 MJ/kg respec-tively. Coefficient of thermal conversion is 0.84, 0.68, and 0.60 for gasification of wood, Pongamia shells, and Pongamia deoiled cakes respectively. An integrated system involving gasifier, spark ignition engine, oil expeller, and decorticator is tested success-fully within 3 hours continuous operation of gasifier on waste of oil seeds collections.